Personality traits and level of motivation towards ICT integration in the L2 learning context - Loo, Kien Men; Noordin, Nooreen (Human Resource Management Academic Research Society, 2019)
Today’s digital age offers the Digital Natives unmatched efficiency of learning languages and other fields of knowledge via the use of technology. Many educational policies including the Malaysia Education Blueprint (2013-2025) have taken initiatives to implement ICT in learning to cater to the various learning styles of the Digital Natives. However, findings have shown that the implementation process has not been easy as majority of teachers expressed reluctance in integrating ICT in their lessons as required. This study attempted to find out the levels of ICT integration, personality traits and motivation among undergraduates in the ESL context. Seventy-two undergraduates majoring in Teaching English as a Second Language (TESL) were involved in this quantitative study. A questionnaire and semi-structured interviews were used for data collection. Results show that their level of ICT integration in learning was high. Their level of motivation in integrating ICT in L2 learning was high as well. Next, the sample was reported to score the highest in Openness to experience, followed by Conscientiousness, Agreeableness and Extraversion towards ICT integration in L2 learning while low scores were obtained for Neuroticism. Findings also indicated that there was a significant, moderate, positive relationship between their level of motivation, Agreeableness, Conscientiousness, Extraversion and Openness traits and their ICT integration in L2 learning. These findings present vital implications for program developers at the tertiary level as well course coordinators in facilitating pre-service teachers to leverage ICT in their teaching practice.